2017
DOI: 10.1111/jpn.12780
|View full text |Cite
|
Sign up to set email alerts
|

Bovine colostrum enriched with lyophilized bovine colostrum stimulates intestinal epithelium renewal of Holstein calves in the first days of life

Abstract: Consumption of a second meal of colostrum with high quality could contribute to the intestinal epithelium development, especially if there is poor supply of colostrum just after birth. The effect of a second colostrum meal was evaluated on histomorphometry of the intestinal mucosa of newborn Holstein calves fed with high- and low-quality first colostrum. Seventy-two calves were fed with a first colostrum meal with high (HFM, close to 100 mg/ml) or low (LFM, close to 30 mg/ml) IgG concentration. At 12 hr of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A low-dose of BC supplementation diminishes inflammatory indices following in soccer players ( Kotsis et al, 2018 ). Several intact proteins that enriched in colostrum, such as immunoglobulins, lactoferrin, and growth factors, exert their effect directly in the intestine ( Kindlein et al, 2018 ). Lactoferrin and immunoglobulins are partially resistant to digestive enzymes ( Ontsouka et al, 2016 ) making direct effects feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A low-dose of BC supplementation diminishes inflammatory indices following in soccer players ( Kotsis et al, 2018 ). Several intact proteins that enriched in colostrum, such as immunoglobulins, lactoferrin, and growth factors, exert their effect directly in the intestine ( Kindlein et al, 2018 ). Lactoferrin and immunoglobulins are partially resistant to digestive enzymes ( Ontsouka et al, 2016 ) making direct effects feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown both the short-term and long-term benefits of having adequate TPI in calves ( 16 19 ). It is well-established that calf health and wellbeing, future milk production, and longevity in the herd are highly correlated with successful TPI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies have evaluated the potential role of BC in the health [ 26 , 27 ], energy balance, and sports performance [ 28 ] of humans. Moreover, some studies have also highlighted the beneficial effects of BC supplementation for animals such as mice [ 29 ], rats [ 30 ], horses [ 31 ], piglets [ 32 ], dogs [ 33 , 34 ], lambs [ 35 ], poultry [ 36 ], and calves [ 37 ].…”
Section: Introductionmentioning
confidence: 99%